Treatment for Eosinophilic Esophagitis in adults: where are we? - Campanha Menon Carlos, Gustavo; Martins Ginack, Camilla; Iemini Costa, Giovanna; Martins Ribeiro Ferreira, Lucas; Duarte Cabral, Antônio; Moreira Alves de Souza, Isabella; Zimberg Chehter , Ethel (Seven Editora, 2023)
(1) Eosinophilic Esophagitis (EEo) is a disease that falls within a spectrum of eosinophilic gastrointestinal disorders, the inflammation of which has no secondary causes. (2) EEo is defined as a chronic, inflammatory, antigen-mediated esophageal disease, which can be characterized by clinical symptoms related to esophageal dysfunction, (3) such as dysphagia, vomiting, and food impact (2) and by histology compatible with predominant inflammation of eosinophils. (3) Diagnostic confirmation is confirmed with the presence of 15 or more eosinophils per highly increased field in esophageal biopsies performed via upper digestive endoscopy (EDA) and the absence of eosinophilic infiltrate in the other segments of the digestive tract. DOI: https://doi.org/10.56238/devopinterscie-150